1-(3-Methyl-3-mesityl)-cyclobutyl-2-(5-pyridin-4-yl-2H-[1,2,4]triazol-3-ylsulfanyl)-ethanone: X-ray structure, spectroscopic characterization and DFT studies - Inkaya, Ersin; Dincer, Muharrem; Ekici, Oner; Cukurovali, Alaaddin (Pergamon-Elsevier Science Ltd, 2013)
The triazole compound 1-(3-Methyl-3-mesityl)-cyclobutyl-2-(5-pyridin-4-yl-2H-[1,2,4]triazol-3-ylsulfanyl)-ethanone, (C23H26N4OS), was characterized by X-ray single crystal diffraction technique, IR NMR spectroscopy and quantum chemical computational methods as both experimental and theoretically. The compound crystallizes in the monoclinic space group P2(1)/c with Z = 4. The molecular geometry was also optimized using density functional theory (DFT/B3LYP) method with the 6-311G(d,p) basis set in ground state and compared with the experimental data. The computed vibrational frequencies are used to determine the types of molecular motions associated with each of the experimental bands observed. The results of the calculations were applied to simulate spectra of the title compound, which show excellent agreement with observed spectra. Data of the title compound display significant structure correlation and provide the basis for future design of efficient materials having the derivatives of 1,2,4-triazole. From the optimized geometry of the molecule, vibrational frequencies, gauge-independent atomic orbital (CIAO) H-1 and C-13 NMR chemical shift values, molecular electrostatic potential (MEP) distribution, non-linear optical properties and frontier molecular orbitals (FMOs) of the title compound were performed at B3LYP/6-311G(d,p). On the basis of theoretical vibrational analyses, the thermodynamic properties (standard heat capacities, standard entropies, and standard enthalpy changes) of the title compound at different temperatures have been calculated, revealing the correlations between C-p,m(0), S-m(0), Delta H-m(0) and temperatures. The predicted non-linear optical properties of the title compound are much greater than those of urea. Data of the title compound display significant structure-correlation and provide the basis for future design of efficient materials having the derivatives of 1,2,4-triazole. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: X-ray structure determination; IR and NMR spectroscopy; DFT calculations; [1,2,4] Triazole; Cyclobutane; Non-linear optical properties